2019
DOI: 10.1002/cam4.2060
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue and physical activity in cancer survivors: A cross‐sectional population‐based study

Abstract: Purpose A substantial proportion of cancer survivors experience fatigue after diagnosis. Physical activity (PA) can impact fatigue after cancer. In this study, we evaluated the prevalence and association of fatigue and the practice of PA in a population with early cancer. Methods Using the national population‐based French cross‐sectional study Vie après le cancer 2 , we included 1984 patients with early breast (61.1%), prostate (21.5%), and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 46 publications
2
13
1
Order By: Relevance
“…Our study found no beneficial effects of pre-diagnosis PA on long-term fatigue. This is in in line with a French study [19] which also used the EORTC QLQ-C30 fatigue subscale. That study, which included CRC survivors, also did not find an association between pre-diagnosis PA and fatigue in cancer patients 2 years after diagnosis.…”
Section: Relationship With Previous Findingssupporting
confidence: 88%
See 1 more Smart Citation
“…Our study found no beneficial effects of pre-diagnosis PA on long-term fatigue. This is in in line with a French study [19] which also used the EORTC QLQ-C30 fatigue subscale. That study, which included CRC survivors, also did not find an association between pre-diagnosis PA and fatigue in cancer patients 2 years after diagnosis.…”
Section: Relationship With Previous Findingssupporting
confidence: 88%
“…Although one study [19] investigated the association of pre-diagnosis PA and fatigue 2 years after diagnosis so far, no study has investigated associations of pre-as well as post-diagnosis PA with fatigue specifically in longterm (≥5 years post-diagnosis) CRC survivors. Moreover, the available evidence regarding the association between PA and fatigue among CRC survivors is mainly based on studies with a cross-sectional design [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Sixty percent of survivors of breast cancer reported moderate-to-severe tiredness 12 months after diagnosis [ 24 ]. Between 21% and 52% of survivors still experience severe CRF up to 3 years post-diagnosis [ 18 , 25 , 26 ].…”
Section: Prevalence Of Crfmentioning
confidence: 99%
“…Our results are consistent with robust evidence Open access that fatigue is a common problem across populations of cancer survivors with prevalence as high as 40% and is the most common adverse event in patients on CIs. [15][16][17][18][19] Findings regarding fatigue in melanoma survivors are mixed.…”
Section: Open Accessmentioning
confidence: 99%